Penerapan Penelitian Tindakan Kelas Cooperative Learning Tipe Peer Teaching untuk Meningkatkan Keterlibatan Siswa dalam Pembelajaran Biologi - Nory Shenta Dewi; Murni Ramli; Yudi Rinanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The research aims to increase students' engagement in Biology learning by applying cooperative learningmethod specifically peer teaching. The subjects consisted of 32 high school students focusing on LowAchievement (LA) and High Achievement (HA) students. This research is classroom action research (CAR)with 3 Cycles. The research procedure includes the stage of reflection, planning, implementation of action andobservation. Behavioral Engagement (BE) data obtained through observation, other data in the form ofPsychological Engagement (PE) and Cognitive Engagement (CE) obtained through student engagementquestionnaire based on Student Engagement Instrument (SEI). Technique of data validation used istriangulation technique. Technique of analysis data performed by data reduction, data presentation and drawingconclusions based on qualitative descriptive analysis. The results showed that cooperative learning methodspecifically peer teaching can increase student engagement in biology learning. The average percentage of allBE aspects observed in LA students before the treatment given, Cycle I, Cycle II and Cycle III respectivelywas 13.72%; 35.24%; 48.26% and 64.24% respectively. Meanwhile BE results of HA students before thetreatment given, Cycle I, Cycle II and Cycle III respectively were 22.22%; 48.97%; 56.6% and 64.76%respectively. The results of PE of LA students before the treatment given to Cycle III increased by 3.54% whilePE in HA students before the treatment given to Cycle III increased from 3.75%. The result of CE analysis ofLA students has increased before the treatment given toward Cycle III that is 2.94% while in HA studentsincreased by 2.95%.